Rebellion as a Quasi-Criminal Activity. - Collier, P (2000)
Economic models of rebellion usually treat it as a form of crime or banditry. However, the analogy is not developed. This article treats rebellion as a distinctive form of organized crime that differs from other crime in its objective, which is the predation of the rents on natural resource exports. Because such rents can be defended by government forces, rebel forces must be sufficiently large to defend themselves. This introduces a survival constraint that affects whether a rebellion is financially viable and how it reacts to increases in government forces and introduces an entry threshold. This threshold gives rise to a problem for the rebellion of attracting sufficient start-up finance. The predictions of the model are shown to be consistent with four stylized facts.